Penyusunan Masterplan Objek Wisata Spiritual Alas Metapa Desa Peninjoan Bangli - I Gusti Bagus Suryawan; I Wayan Wirya Sastrawan; I Wayan Arthanaya (Universitas Warmadewa, 2023)
Peninjoan Village has the potential in the form of Alas Metapa natural springs which are worthy of being developed into new tourist attractions in the form of Spiritual Tourism Objects and Water Parks. The purpose of this PKM is as a concrete form of one of the Tri Dharma of Higher Education, namely Community Service. During the PKM implementation process at the Alas Metapa Object, there are several conclusions that can be drawn, among others, the Alas Metapa Object arrangement masterplan drawing that was approved during the FGD and will subsequently be made a detailed DED drawing of each part of the nista, madya, and main mandala. PKM partners and the local community are very cooperative in providing data needs related to the potential and problems that are the basis for the PKM Team in solving problems. Suggestions that can be conveyed by the PKM Team during this PKM activity are the involvement of the PKM Team and architectural experts only in planning, but in the development implementation stage it is no less vital so that the hope is that what is planned can be carried out properly and as expected.